Penguatan Kepercayaan Diri Anak dengan Pelatihan Dasar Kepemimpinan Forum Anak Tingkat Kota Tangerang - Supriadi, Yudi Nur; Rialmi, Zackharia; Kusuma, Jaka Wijaya; Hamidah, Hamidah (Jurnal Pengabdian UNDIKMA, 2022)
The purpose of this community service is to strengthen children’s self-confidence with counseling and basic leadership training.Â The method of implementing the service activity is offline training which is carried out at the Tangerang Regional Government Hall. The target of the service activity is the City Children’s Forum, Tangerang. The community service team is from the Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta in collaboration with Bina Bangsa University and the Office of Women’s Empowerment, Child Protection, Population Control and Family Planning of Tangerang City. The instruments used as activity evaluations are questionnaires for children’s responses to activities and questionnaires for children’s self-confidence after being given training and counseling. The data analysis uses the percentage of responses and then determines the category. The results and conclusions of devotion are: 1) children’s response to service activities is 85%, which is classified as very good. This means that the children’s forum who are respondents in this service consider that counseling activities and basic leadership training make a positive contribution to their knowledge of leadership; 2) the majority of children’s self-confidence is high and moderate after receiving counseling and basic leadership training.